Pelatihan Motivasi Belajar dengan Metode Roleplay pada Siswa SDN Karangsegar 02 Kabupaten Bekasi - Rofieq, Ainur; Lucky Purwantini; Debby Aureli Rahmadani; Siti Asiah (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Educators must prioritize the development of motivation among students, particularly those in the sixth grade. This is because these students are likely to continue their education to a higher level and therefore require a solid foundation of motivation to excel. Without efforts to enhance their low learning motivation, these students will encounter difficulties at the subsequent educational level. The objective of this community service is to enhance the learning motivation of sixth-grade students at SDN Karangsegar 02 in Bekasi Regency. A total of 15 sixth-grade students whose pretest results indicated low scores on the learning motivation scale will participate in a community service activity. The instrument used is the Academic Motivation Scale - Indonesian Short Version, which has a reliability of above 0.7. The results of the community service indicated that learning motivation training using the roleplay method was an effective approach for increasing students' learning motivation.